Analysis of Differentiated Learning Needs in Mathematics Subjects in Class 5 of SDN 182 North Bengkulu - Herlina, Henny (CV Media Inti Teknologi, 2023)
This research activity aims to analyze the need for differentiated learning in mathematics at SD Kurikulum Merdeka in the fifth grade of SDN 182 North Bengkulu. The utilized research methodology involved a descriptive qualitative approach, employing a case study framework. Data collection encompassed observation, interviews, and document analysis. The findings of the investigation suggest that there is a requirement for implementing distinct approaches to learning mathematics in the fifth grade of Merdeka Curriculum Elementary School, located at SDN 182 North Bengkulu. Several factors underlie this need including the various levels of student understanding, different learning styles, and the diversity of students' abilities and talents in mathematics. Based on data analysis, several differentiated learning strategies that can be applied include (1) the use of learning materials that are varied and vary according to the level of understanding of students, (2) giving assignments or activities based on student's interests and talents, (3) the use of various learning media, (4) heterogeneous study group settings, and (5) providing additional support to students in need. This research is expected to contribute to the development of mathematics learning in Merdeka Curriculum Elementary School in the fifth grade of SDN 182 North Bengkulu, as well as to provide guidance for teachers and education stakeholders in designing effective differentiated learning to improve students' mathematics achievement.